2014
DOI: 10.1007/s13204-014-0384-4
|View full text |Cite
|
Sign up to set email alerts
|

Abroma augusta Linn bark extract-mediated green synthesis of gold nanoparticles and its application in catalytic reduction

Abstract: The bark extract of Abroma augusta Linn is rich in medicinally important phytochemicals including antioxidants and polyphenols. First one step green synthesis of gold nanoparticles (AuNPs) has been described utilizing the bark extract of Abroma augusta L. and chloroauric acid under very mild reaction conditions. The phytochemicals present in the bark extract acted both as a reducing as well as a stabilizing agent, and no additional stabilizing and capping agents were needed. Detailed characterizations of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…This proved that the present catalyst system is effective towards the catalytic reduction of single or bicomponent systems. In 2015, Das et al (2015) reported the k app value of 7 9 10 -3 s -1 for the catalytic reduction of NiP using plant extract decorated Au nanoparticles. When compared with the literature, the present system yielded somewhat higher k app value.…”
Section: Catalytic Reduction Of Cr(vi) Under Different Experimental Cmentioning
confidence: 99%
“…This proved that the present catalyst system is effective towards the catalytic reduction of single or bicomponent systems. In 2015, Das et al (2015) reported the k app value of 7 9 10 -3 s -1 for the catalytic reduction of NiP using plant extract decorated Au nanoparticles. When compared with the literature, the present system yielded somewhat higher k app value.…”
Section: Catalytic Reduction Of Cr(vi) Under Different Experimental Cmentioning
confidence: 99%
“…Additional advantage of this method is that the extract itself acts as a stabilizer and no additional stabilizers are required. The extracts of Aspergillus fischeri [ 19 ], Epicoccum nigrum [ 20 ], bark of Mimusops elengi [ 21 ], leaf of Chrysophyllum cainito (Star apple) [ 22 ], bark of Abroma augusta Linn, [ 23 ] Backhousia citriodora [ 24 ], Breynia rhamnoides [ 25 ], Piper betle [ 26 ], pear extract [ 27 ] etc. have been utilized for the synthesis of AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the plant extract itself acts as a stabilizer, it makes the method more advantageous over other synthetic methods. The extracts of Acacia nilotica leaf (Majumdar and Bag 2013), Lantana camara leaf (Dash et al 2014a), Abroma augusta Linn bark (Das et al 2014), Breynia rhamnoides (Gangula et al 2011), Saraca indica (Dash et al 2014b), Piper betle (Punuri et al 2012), green coconut shell (Paul et al 2014), etc., have been utilized for the synthesis of AuNPs. During our investigations on the utilization of triterpenoids (C30s) as renewable functional nano-entities Bag and Dash 2011;Bag and Paul 2012;Bag and Majumdar 2014), it occurred to us that the medicinally important bark extract of Mimusops elengi, rich in polyphenolic compounds, can be utilized for the synthesis AuNPs from HAuCl 4 (Baliga et al 2011;Kadam et al 2012).…”
Section: Introductionmentioning
confidence: 99%